A Hybrid Model Based on DNA Method for Encryption Messages and Hiding Secret Keys in Cover Image - Hussein, Asraa Abdullah; Al Baity, Rafeef M.; Ajam, Noura H. (Iraqi Journal of Science, 2025)
Due to the continuous development of information technology and the widespread exchange of digital media, such as text, videos, and images, between parties, protection has become a necessity. In addition, with the latest modern technology, copying and using information illegally has become elementary. In the research community, the given scenario imposes challenges to transferring multimedia files more securely. In such scenarios, various techniques, such as cryptography and steganography, protect secret data from adversaries. The use of biology in cryptography is a new approach to cryptographic research. This paper will present a method of cryptography inspired by DNA structure and its relationship to amino acids. Work has been done on one of the most practical, effective, and modern methods to develop encryption and decryption algorithms, which is DNA-based encryption. Three steps make up the proposed system firstly, the message text is initially hidden in a randomly generated string until it is  encrypted. Secondly: encode the message using amino acids and DNA codes. In the third stage, the encryption key is hidden in the cover image using the least significant bit (LSB). The new encryption technology demonstrated several levels of protection by encrypting amino acids and DNA and hiding the encryption keys in the cover image. Moreover, the PSNR metrics used for analysis and comparison show that the proposed approach provides good security.